Teaching profession : passion and mission - Pawilen, Greg Tabios (Manila, Philippines : Rex Book Store, 2016)
This book is about the Teaching Profession. The teaching profession is as old as life itself. Teaching is an integral part of everyday life. These people are driven by a deep passion an a great sense of mission to serve humanity by giving their lives, services, talents, skills, and wisdom to help individuals have a dignified life and discover the secrets of the universe.
Chapter 1. The teacher as a person in the society -- Chapter 2. Teaching competencies -- Chapter 3. Challenges in teaching -- Chapter 4. Legal bases of the teaching profession.
Includes bibliographical references and index.
Keywords: TEACHING -- PASSION -- MISSION